Into the newsroom : - Teel, Leonard Ray (Prentice-Hall, 1983)
The book explains how a magazine functions on a day-to-day basis and shows how to develop articles and designs from the initial concept through publication, including valuable tips on developing a subscription base, selling advertising space, promoting a magazine.